(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVE: This study evaluated whether smear layer removal has any influence on the filling of the root canal system, by examining the obturation of lateral canals, secondary canals and apical deltas. MATERIAL AND METHODS: Eighty maxillary and mandibular canines were randomly divided into two groups, according to their irrigation regimen. Both groups were irrigated with 1% NaOCl during canal shaping, but only the teeth in Group II received a final irrigation with 17% EDTA for smear layer removal. The root canals were obturated with lateral condensation of gutta-percha and the specimens were cleared, allowing for observation under the microscope. RESULTS: In Groups I and II, 42.5% and 37.5% of the teeth, respectively, presented at least one filled canal ramification. Although a larger number of obturated ramifications was found in Group I, there were no statistically significant differences between the two groups (p = 0.4957). CONCLUSIONS: Smear layer removal under the conditions tested in this study did not affect the obturation of root canal ramifications when lateral condensation of gutta-percha was the technique used for root canal filling.